FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN NYATA E-COMMERCE SEBAGAI MEDIA PENJUALAN BARANG STUDI KASUS USAHA PENGRAJIN SEPATU SANDAL DAN TAS DI KOTA BOGOR - Alawiah, Enok Tuti (Jurnal Pilar Nusa Mandiri, 2014)
Factors Affecting the Use of Real E-commerce For Sale of Goods Media. This study aims to determine the Factors Affecting Interests Using E-commerce For Sale of Goods Media. The model used is the Technology Acceptance Model. Factors thought to have an influence on actual usage is Computer Self Efficacy, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Intention to Use and Actual Usage. This study aimed to measure the actual usage of e-commerce in enterprises craftsmen Shoes and Bags in Bogor. All variables influence hypothesis, but there are some indicators that lost in the final model due to no more valid results valid. For longer needed another indicator as a supporter.